2023
DOI: 10.1039/d2ja00382a
|View full text |Cite
|
Sign up to set email alerts
|

Highly sensitive determination of arsenic in water samples by hydrogen-doped solution anode glow discharge-optical emission spectrometry

Abstract: In this work, a new method based on hydrogen-doped solution anode glow discharge optical emission spectrometry (SAGD-OES) was developed for the direct detection of trace As in water samples. It...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 53 publications
0
8
0
Order By: Relevance
“…It is produced by capturing cosmic-ray-induced thermal neutrons a few metres below the Earth's surface. Aer several half-lives (∼99 ka) of exposure the 41 Ca/Ca ratio approaches a saturation value. Surface samplesbiological or geologicalwhen buried deeper than this level will be isolated from further 41 Ca growth and hence it will decay: which means that low levels of 41 Ca reect longer burial.…”
Section: New Developmentsmentioning
confidence: 95%
See 1 more Smart Citation
“…It is produced by capturing cosmic-ray-induced thermal neutrons a few metres below the Earth's surface. Aer several half-lives (∼99 ka) of exposure the 41 Ca/Ca ratio approaches a saturation value. Surface samplesbiological or geologicalwhen buried deeper than this level will be isolated from further 41 Ca growth and hence it will decay: which means that low levels of 41 Ca reect longer burial.…”
Section: New Developmentsmentioning
confidence: 95%
“…Direct determination of As was also reported using an H 2 -doped SAGD. 41 It was found that efficient vapour generation and excitation of As could be achieved simultaneously in an Ar–H 2 SAGD, contributing to the significant improvement in As signal sensitivity, compared to that in SAGDs without H 2 doping or SCGD, and eliminating the need for HG. Under optimal operating conditions, the LOD for As was found to be 1.4 μg L −1 (193.7 nm), with good calibration linearity in the range of 5–500 μg L −1 .…”
Section: Liquids Analysismentioning
confidence: 99%
“…Two groups of researchers applied GD-OES to the analysis of drinking water 123 and other beverages. 124 To achieve improved sensitivity for the determination of As in water, Liu et al 123 introduced a hydrogen-doped solution anode to perform GD-OES (SAGD-OES).…”
Section: Progress With Analytical Techniquesmentioning
confidence: 99%
“…Two groups of researchers applied GD-OES to the analysis of drinking water 123 and other beverages. 124 To achieve improved sensitivity for the determination of As in water, Liu et al 123 introduced a hydrogen-doped solution anode to perform GD-OES (SAGD-OES). This arrangement allowed simultaneous efficient volatilisation and excitation of As, as well as elimination of the need for an HG sampling unit and related chemicals .…”
Section: Progress With Analytical Techniquesmentioning
confidence: 99%
“…[21][22][23][24][25] Several compact and cost-effective instruments based on microplasma excitation sources have been developed, including atmospheric pressure solution cathode glow discharge (ELCAD) 26,27 /solution cathode glow discharge (SCGD), dielectric barrier discharge (DBD), 28,29 atmospheric pressure glow discharge (APGD), 30,31 point discharge (PD) [32][33][34][35] and solution anode glow discharge (SAGD). 36,37 ELCAD/SCGD operate between a metal anode and a owing dynamic cathode glow discharge, allowing the detection of various elements without the need for inert gas like Ar or He. This makes them more suitable for the development of portable instruments.…”
Section: Introductionmentioning
confidence: 99%